PERANAN LEMBAGA KEMASYARAKATAN KELURAHAN SEBAGAI MITRA KERJA LURAH DI KELURAHAN PAGESANGAN KECAMATAN MATARAM KOTA MATARAM PROVINSI NUSATENGGARA BARAT - Rosshad, Anwar; Dewantara, Diki (Fakultas Politik Pemerintahan, 2019)
The Role of Village Community Institutions as Village Work Partners in Pagesangan Sub-District, Mataram District, Mataram City, West Nusa Tenggara Province. Decentralization has caused some central government affairs to be delegated to regional government affairs. One of them is basic and social services. The purpose of this study is to describe the role of Village Community Institutions as working partners of headman in Pagesangan Sub-District, Mataram Subdistrict, in basic services to the community and in the social field in the Village. The research method used is an explorative method with an inductive approach that aims to obtain information about the current situation by looking at the links between the variables that exist. Data collection techniques include observation, interviews and documentation. Data analysis is done by data reduction, data presentation and conclusion drawing. The results of the study illustrate the role of the Pagesangan Village community institution as a working partner of the village head both in the field of service and social affairs, although there are still obstacles. Suggestions given to Pagesangan Village and village community institutions are to make further technical implementation guidelines on the role of villagesocial institutions, improve work motivation, improve socialization and service quality, and increase community independence and role in social services and activities in the Village Pagesangan.